A Survey: Computing Iceberg Queries - Ravi, Pallam; Haritha, D; Niranjan, P (International Journal of Engineering and Technology, 2018)
Knowledge discovery, tasks are deals with huge no of records. Queries are needed to identify unique attributes values and their aggregate that is above a predefined threshold from this huge number of records. This type of queries is called iceberg queries. Iceberg queries requires huge amount of main memory and takes longer time to answer the query. As computer system has limited amount of main memory, the processing of iceberg queries is a challenging task. This paper discusses different methods that are in literature for processing iceberg queries , we also explore pros and cons of these methods and   future scope.